Parent reported home smoking bans and toddler (18–30 month) smoke exposure: a cross-sectional survey. Issue 7 (21st June 2005) - Spencer, N; Blackburn, C; Bonas, S; Coe, C; Dolan, A
Abstract : Aims: To study the relation between the use of parent reported home smoking bans and smoke exposure among children aged 18–30 months. Methods: A total of 309 smoking households with children aged 18–30 months, who were part of the Coventry Cohort study, consented to participate in this cross-sectional survey. Results: Although parents in almost 88% of smoking households reported using harm reduction strategies to protect their toddlers from smoke exposure, only 13.9% reported smoking bans in the house. Mean log urinary cotinine:creatinine ratio was significantly lower for those children whose parents reported no smoking in the house (1.11, 95% CI 0.64 to 1.49) compared with none/less strict strategies (1.87, 95% CI 1.64 to 2.10). In linear regression models fitted on log cotinine:creatinine ratio, no smoking in the house was independently associated with a significant reduction in cotinine:creatinine ratio (B = −0.55, 95% CI −0.89 to −0.20) after adjusting for mother's and partner's average daily cigarette consumption, housing tenure, and overcrowding. The final model accounted for 44.3% of the variance. Conclusions: Not smoking in the house was associated with a reduction in mean urinary cotinine:creatinine ratio in children aged 18–30 months; the relation persisted after adjustment for levels of mother's and partner's daily cigarette consumption and sociodemographic factors. Results suggest that home smoking bans in this age group have a small but significant effect on smoke exposure independent of levels of parental tobacco consumption.